Retrospective analysis of intrauterine granulocyte colony-stimulating factor in controlled ovarian stimulation with intrauterine insemination cycle - Nayak, Navinchandra R.; T., Madhumeetha; Hegde, Mangala Gowri; Aravind, Aparna C.; A., Ritu Sharma; K., Shwetha Ballal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Persistent thin endometrium affects <1% of patients. Various treatments have been proposed with no satisfactory results. GCSF is one such treatment modality which improves endometrial thickness and implantation. Aim of this study was to analyse the effects of dose and the site of instilling intrauterine G-CSF in COS IUI cycles in patients with unexplained infertility and to note the pregnancy rates among them. Methods: It is a 3-year retrospective study done in obstetrics and gynecology department of AJ Institute of Medical Sciences and Research Centre, that included all unexplained infertility cycles with controlled ovulation stimulation-IUI protocols where for a thin endometrium GCSF was used. The method of ovarian stimulation, the drug and dose used, the trigger for ovulation and the ovarian and endometrial response was noted. The day of the intrauterine GCSF and the dose and the site of instillation was noted. The endometrial response to GCSF the outcome for pregnancy was noted. All the data was analyzed statistically. Results: Significant endometrial response was seen with a dose of 100 mg,150 mg and 300 mg. Pregnancy outcome was better when GCSF was instilled just above the level of the os. GCSF instilled at the level of the fundus increases the possibility of ectopic pregnancy. Conclusions: Instillation of GCSF of 100 mg dosage just above the os; is a safe and effective method for improving the endometrial thickness and increasing pregnancy rate.